The Complexity Theory as an epistemological reference for research in educational policy: (re)knowing its principles and characteristics - Roberta Cajaseiras de Carvalho; Altair Alberto Fávero (Red Latinoamericana de Estudios Epistemológicos en Política Educativa, 2020)
The purpose of this text is to point out the complexity theory as an epistemological reference for educational policy studies. The motivation for the research is the search for epistemological references that are able to unveil the methodological possibilities beyond theoretical or empirical isolation, in which they promote an "Applied Rationalism", proposed by Gastón Bachelard (1978, 1985). Thus, the epistemological originality stimulation by educational policy researchers is sought, emphasizing the starting point with conscious and critical theoretical training. The study is the partial result of a qualitative exploratory research, in terms of objectives and theoretical-bibliographic in terms of procedures, it is structured as follows: in the first part, the principles and characteristics of complexity theory are presented; in the sequence, a differentiation is made between the traditional paradigm of education systems and complexity theory; Finally, the delimited principles of complex systems that enable a broader sense of studying and understanding educational policy are presented.